SOCIOECONOMIC AND PHYSICAL DETERMINANTS OF PLACE PERFORMANCE IN GREEN-CERTIFIED BUILDINGS IN LAGOS, NIGERIA - Ayoola, Abayomi; Ayinla, Abdulrasaq; Ajayi, Oluwole; Makinde, Olusola (FUDMA Journal of Sciences, 2026)
This study investigates the socioeconomic and physical determinants of place performance in green-certified buildings in Lagos, Nigeria, focusing on the relationship between building condition, user characteristics, and occupant experience. A mixed-methods post-occupancy evaluation approach was adopted using structured questionnaires and building assessment across nine LEED and EDGE-certified buildings. Data from 1,004 valid responses were analyzed, and a composite Building Condition Index (BCI) was developed. Findings revealed that the buildings generally performed well in building materials, energy efficiency, water efficiency, and waste management, achieving an overall BCI of 4.02/5.0. However, performance was primarily driven by operational efficiency measures, while advanced sustainability features such as renewable energy systems, water reuse, and waste-to-energy technologies were limited. Income showed the strongest association with green-building occupancy (χ²=748.22, V=0.70), while occupation, age, education, ethnicity, and household size significantly influenced accessibility and perception; gender was not significant. ANOVA revealed significant performance differences among buildings (F=208.37, p
Keywords: Green-certified buildings; Place performance; Building Condition Index; Post-occupancy evaluation; Socioeconomic determinants